Carsharing in the Brussels region - Mareile Wiegmann; Imre Keserü; Cathy Macharis (Brussels Studies, 2020)
The aim of this fact sheet is to highlight the differences and commonalities between the user profiles of station-based and free-floating carsharing services based on the analysis of a survey of 5 375 car sharing users in Brussels. The analysis shows that free-floating users have a higher rate of car ownership, higher share of males and they are slightly younger. Both types of services cater to individuals with a high level of education and are used approximately 1 to 3 times a month. The two services clearly serve different purposes, with a greater variety of travel motives stated by the users of free-floating services and the rates of car ownership much higher. In addition, users reportedly reduce their car use once they become members, while the impact on public transport use remains unclear, with free-floating users replacing public transport trips partly with carsharing.